Multiple Marginal Tissue Recession Treated with a Simplified Lateral Sliding Flap Technique - Fernando Salimon Ribeiro; Juliana Aparecida Najarro Dearo de Morais-Camillo; José Marcos Alves Fernandes; Juliana Rico Pires; Elizangela Partata Zuza; Ana Emília Farias Pontes (Case Reports in Dentistry)
Marginal tissue recession is a common esthetic problem that is usually accompanied by dentin sensitivity, and patients frequently report a fear of dental loss. Lateral sliding flaps have been used for localized recession, but they are rarely used for multiple recessions. The aim of this paper was to report a case of coverage of multiple marginal tissue recessions by means of a lateral sliding flap associated with a connective tissue graft. This was a modification of Nelson’s technique, which was originally described as the combination of the double papilla technique, lateral sliding flap, and connective tissue graft. In the present case, double papilla was not performed, rendering the maneuver less complicated. After surgery on teeth #23 to #25, total root coverage, decreased dentin sensitivity, and increased keratinized tissue band and gingival thickness were achieved. In the present case, modified Nelson technique proved to be a more simple procedure for the treatment of multiple recessions in one session, resulting in adequate healing, predictable root coverage, and, more importantly, esthetic and functional success.